Investigation of antioxidant and detoxifying capacities of some date cultivars (Phoenix dactylifera L.) irrigated with sewage water. Issue 21 (24th February 2017) - Abdulaal, Wesam H.; Zeyadi, Mustafa; Baothman, Othman A. S.; Zamzami, Mazin A.; Choudhry, Hani; Almulaiky, Yaaser Q.; Saleh, Rashad M.; Mohamed, Saleh A.
Abstract : The objective of the study was to compare the effect of irrigation by municipal water (MW) and sewage water (SW) on antioxidant and detoxifying capacities of some commercial Saudi date cultivars, Agwa, Anbr and Safawi ( Phoenix dactylifera L.). Abstract : The objective of the study was to compare the effect of irrigation by municipal water (MW) and sewage water (SW) on antioxidant and detoxifying capacities of some commercial Saudi date cultivars, Agwa, Anbr and Safawi ( Phoenix dactylifera L.). Higher amounts of phenolic and flavonoid were detected in dateSW compared with dateMW . The levels of accumulation of heavy metals in dateSW were higher than those of dateMW . The phenolic extracts of dateSW exhibited higher antioxidant activity using 1, 1-diphenyl-2-picrylhydrazyl (DPPH), 2, 2′-azinobis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and the formation of phosphomolybdenum complex tests than those detected in dateMW . In the same manner, the activities of peroxidase, polyphenoloxidase and glutathione- S -transferase of dateSW were higher than those exhibited in dateMW . The higher levels of all these examined parameters, induced by sewage wastewater contaminants, may be contribute to protecting dateSW from oxidative and toxicity stresses.